The Effect of Product Quality on Repurchase Interest Mediated by Consumer Satisfaction of Lemonilo Noodles in Cimahi City - Sarah Tirta Permana; Vita Dhameria (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2025)
This study aims to analyze the influence of product quality on repurchase interest with consumer satisfaction as an intermediate variable among students in Cimahi City. A sample of 60 respondents was obtained through purposive sampling. Data were collected using questionnaires and quantitatively processed with the Sobel Test using SPSS software version 27. The results show that product quality has a significant influence on consumer satisfaction, product quality has a significant influence on repurchase intention, consumer satisfaction has a significant influence on repurchase intention, and consumer satisfaction is proven to have a significant mediating role in the relationship between product quality and repurchase intention. The uniqueness of this research lies in its focus on examining the mediating role of consumer satisfaction in the context of students in Cimahi City, thereby providing new insights for the marketing literature by highlighting local perspectives that are rarely studied. This research contributes to three aspects. First, strengthen the theory of consumer behavior by proving that satisfaction mediates the relationship between product quality and repurchase interest, and enriches empirical studies on the role of product quality in consumer satisfaction and loyalty (especially students). Second, becomes a guideline for business actors in Cimahi City to improve product quality. Third, the application of the Sobel Test contributes to analyzing the role of mediation and can be a reference for future consumer behavior research.